Effect of Fish Meal Level on Growth, Food Digestibility and Fur Properties of Farmed Mink (Mustela vison) - Korhonen, HT; Niemelä, P (ANIMAL PRODUCTION, 2012)
Abstract. Our study sought to determine the effects of normal vs high fish meal levels in the diet on the growing-furring process and apparent food digestibility of farmed male mink (Mustela vison). The subjects were two groups of juvenile dark mink born in May and weaned in August. The experiment started after weaning with two diet groups: (1) normal level of fish meal (NOR), i.e. 4.5% of diet, and (2) high level of fish meal (HIGH), i.e. 10.0% of diet. We found that the mink on the high fishmeal (HIGH) diet consumed slightly more fresh food than the mink on the normal fishmeal diet (NOR) (total consumption 30.6 kg vs 28.1 kg). The mink in the NOR group ingested almost the same amount of food as dry matter and energy as the mink in the HIGH group. On October 22, the body weights of the HIGH group animals were significantly higher than those of the NOR animals. At the final weighing on December 3 (at pelting), a tendency for the body weights of NOR mink was noted to be lower than those of HIGH mink. Skin length was significantly shorter in NOR than in HIGH mink. The number of white wool skins (i.e. fur defect) was higher in NOR than in HIGH mink (4 vs 2 skins). Statistically significant differences in other fur variables were not found between the groups. The apparent digestibility of protein, fat and organic matter was significantly better in HIGH than in NOR mink. Our findings tempt us to conclude that the proportion of fish products, at least those of fishmeal, can be increased in the diet of farm-raised juvenile mink.Keywords: farm-raised mink, feeding, fish products, diet, growing-furring periodAnimal Production 14(1):63-69, January 2012